Late-onset posttransplant Epstein-Barr virusrelated lymphoproliferative disease after cord blood transplantation for chronic active Epstein Barr virus infection: A case report. Issue 12 (25th March 2022) - Yamamoto, Masayo; Shindo, Motohiro; Funayama, Takuya; Sumi, Chihiro; Saito, Takeshi; Toki, Yasumichi; Hatayama, Mayumi; Imadome, Ken-Ichi; Mizukami, Yusuke; Okumura, Toshikatsu
Abstract: Introduction: Posttransplant lymphoproliferative disease (PTLD) is a critical complication of hematopoietic stem cell transplantation (HSCT). PTLD is classified into early and late-onset PTLDs. In post-HSCT patients, late-onset PTLD is rare, particularly PTLD after HSCT for Epstein-Barr virus (EBV)-related lymphoproliferative disease. Here, we report the case of a patient diagnosed with late-onset EBV-related hemophagocytic lymphohistiocytosis (HLH), that of PTLD, after HSCT for chronic active EBV infection (CAEBV), that of EBV related lymphoproliferative disease, probably because of EBV reactivation. Patient concerns and diagnosis: A 22-year-old woman with abdominal fullness visited our hospital. Blood examination showed pancytopenia with atypical lymphocytes, liver dysfunction, and elevated lactate dehydrogenase level. In contrast, bone marrow aspiration showed slight hemophagocytosis with increased natural-killer cells (NK cells). As serum antibodies against EBV were atypical, we calculated the EBV-DNA level in peripheral blood and this level was significantly high. EBV was infected with NK cells, and EBV's monoclonality in NK cells was confirmed. Thus, the patient was diagnosed with CAEBV Interventions and outcomes: The patient received chemotherapy and cord blood cell transplantation (CBT); CAEBV was well controlled. Approximately 6years from CBT for CAEBV, she visited our hospital because of fever. Blood examination revealed pancytopenia with atypical lymphocytes, liver dysfunction, and elevated lactate dehydrogenase level. In contrast, bone marrow aspiration showed hemophagocytosis with increased B and T cell counts without increased NK cell count. Additionally, serum antibody titers against EBV were atypical, and the EBV-DNA level in the peripheral blood was high. EBV was infected with only B cells, and EBV's monoclonality was confirmed. A more detailed analysis indicated that EBV-specific cytotoxic T lymphocytes were inactive. Therefore, she was diagnosed with late-onset EBV-related HLH. She received extensive treatment, but EBV-related HLH did not improve. Finally, she died about 3 weeks after diagnosis. Conclusion: PTLD, including HLH, is a life-threatening complication after transplantation, including HSCT. To our knowledge, this is the first case of late-onset EBV-related HLH after CBT for CAEBV. Late-onset PTLD has an indolent clinical course, but our patient's disease course was extremely aggressive. Therefore, late-onset EBV-related PTLD may be life-threatening.